The cumulated ambulation score is superior to the new mobility score and the de Morton Mobility Index in predicting discharge destination of patients admitted to an acute geriatric ward; a 1-year cohort study of 491 patients. Issue 8 (10th April 2022) - Aagesen, Maria; Kristensen, Morten Tange; Vinther, Anders
Abstract: Purpose: To investigate the predictive value of New Mobility Score, de Morton Mobility Index, and Cumulated Ambulation Score regarding discharge destination, and to determine the feasibility of the tests in an acute geriatric ward. Materials and methods: Observational 1-year cohort study of 491 geriatric patients admitted consecutively from own home. New Mobility Score (pre-hospital functional level), de Morton Mobility Index, and Cumulated Ambulation Score were recorded at the first physiotherapy contact. Results: Univariable logistic regression showed that the odds for not being discharged home were 7 times higher (odds ratio = 7.6, 95%CI; 4.5–12.7) for patients with a non-independent mobility level (Cumulated Ambulation Score ≤ 5) compared to independent (Cumulated Ambulation Score = 6). Corresponding ratios were 6.2 (3.8–10.0) for de Morton Mobility Index ≤ 41 points and 2.8 (1.8–4.5) for New Mobility Score ≤5 points. Adjustment for gender, age, cause of admission, and marital status improved the predictive value of the Cumulated Ambulation Score. Upon admission, 99% of the patients were assessed with New Mobility Score, 100% with Cumulated Ambulation Score, and 81% with de Morton Mobility Index. Conclusion: Cumulated Ambulation Score is more feasible and superior in predicting discharge destination than de Morton Mobility Index and New Mobility Score in an acute geriatric ward. Implications for rehabilitation: Easy, quick, and accurate measurement of mobility is essential for discharge planning and effective targeting of physiotherapy in an acute geriatric ward. The objectively assessed Cumulated Ambulation Score is superior to the de Morton Mobility Index and the pre-hospital New Mobility Score in predicting discharge destination in geriatric patients admitted from their own home. The Cumulated Ambulation Score and the New Mobility Score are more feasible and less time consuming to complete in an acute geriatric ward compared to the de Morton Mobility Index.